Estudo da aplicação e desenvolvimento de um gerador termoelétrico para cogeração em automóveis - Santos, Ledson Pedro e (2020)
In this work, we present the application and development of a thermoelectric generator for cogeneration with heat energy released by car exhaust through the seebeck effect. The current situation of increasing energy demand has driven the search for new forms of energy generation to meet this demand with the use of environment conservation and the Seebeck effect which consists in the production of electricity from a different temperature mode. Applying this thermoelectric generator to a conventional car generates an overall increase in efficiency by reusing the energy that comes from a lost thermal source and it is also possible to apply this thermoelectric generator on the combustion engine hybrid cars giving greater engine autonomy and both cases resulting in reduction of fuel consumption. In this work, an analysis of the energy loss around the thermoelectric generator was made, with the study of the thermoelectric generation by the differential temperature around the prototype setting around automobiles and collected all the results. Based on the configurations of the results obtained for the electrical generation in the prototype and the potential value that can be measured, it can be concluded that it is possible to cogenerate from these thermal changes with small investment in the car.